2014
DOI: 10.1108/rpj-03-2012-0027
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of the wrist orthosis design process

Abstract: Purpose -The purpose of this paper is to describe a manufacturing methodology for a wrist orthosis. The case study aims to offer new approaches in the area of human orthoses. Design/methodology/approach -The article describes the utilization of rapid prototyping (RP), passive stereo photogrammetry and software tools for the orthosis design process. This study shows the key points of the design and manufacturing methodology. The approach uses specific technologies, such as 3D digitizing, reverse engineering and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(80 citation statements)
references
References 12 publications
1
67
0
6
Order By: Relevance
“…The laser scanner has the main advantage of fast processing for 3D reconstructions but is more expensive than photogrammetry (Ciobanu et al, 2013b). Both techniques allow the production of hip orthosis with less direct contact with the patient causing less stress with good repeatability (Palousek et al, 2014). Our results showed that both photogrammetry and 3D laser scanners provided adequate quality for 3D reconstruction of dool's hip and legs with suitable accuracy and resolution (Figure 4a, b).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The laser scanner has the main advantage of fast processing for 3D reconstructions but is more expensive than photogrammetry (Ciobanu et al, 2013b). Both techniques allow the production of hip orthosis with less direct contact with the patient causing less stress with good repeatability (Palousek et al, 2014). Our results showed that both photogrammetry and 3D laser scanners provided adequate quality for 3D reconstruction of dool's hip and legs with suitable accuracy and resolution (Figure 4a, b).…”
Section: Discussionmentioning
confidence: 66%
“…While the application of RP in developing countries is still at early stage, some recent studies have investigated feasibility of using AM and RP in the manufacture of orthoses. Palousek et al (2014), Patar et al (2012), Paterson (2013) and Paterson et al (2010;2014a;2014b; have developed new methods to support the mass customization of wrist splints. Jumani et al (2014) used FDM for fabrication of custom-made foot orthoses, and Mavroidis et al (2011) used RP to produce an ankle-foot orthose.…”
Section: Introductionmentioning
confidence: 99%
“…The thickness of the support was equal to 3.5 mm [16]; later, it was increased to 5 mm to improve the stiffness of the device.…”
Section: Methodsmentioning
confidence: 99%
“…High levels of customization can be achieved by following a reverse engineering approach, usually consisting of three main stages [13, 14], which are critically analyzed in [2]: (1) scanning of anatomical parts, (2) processing of the acquired geometry using CAD software, and (3) creation of the device using additive manufacturing technologies. In literature, there are a few studies which analyze the whole hand orthosis realization process [15, 16]; others concentrate on specific stages, taking anatomy acquisition as provided by suitable systems [1719]. In [7], we tested, on healthy subjects, different scanning methodologies and partially solved the problem of occlusions and involuntary motions by a deformable multiview alignment solution.…”
Section: Related Workmentioning
confidence: 99%
“…Once the virtual mask is modelled, it may be manufactured by using any AM technology that has been previously used in a number of medical applications, including design and manufacturing of medical splints for ankle-foot (Pallari et al 2010) (Faustini et al 2008;Mavroidis et al 2011) or wrist (Palousek et al 2014;Paterson 2013). The physical prototype can be later post-processed for particular applications with conventional existing techniques, such as metal spraying for patientspecific face masks necessary for radiography applications in cancer treatment (Deon J. de Beer et al 2005).…”
Section: Introductionmentioning
confidence: 99%